Consumption of ultra-processed foods in the third gestational trimester and increased weight gain: A Brazilian cohort study - Gomes, Caroline De Barros [UNESP]; Malta, Maíra Barreto; Benício, Maria Helena D'Aquino; De Barros Leite Carvalhaes, Maria Antonieta [UNESP] (Cambridge University Press (CUP), 2020)
Objective:To investigate whether the consumption of ultra-processed foods (UPF) during pregnancy is associated with gestational weight gain (GWG).Design:Cohort study with collection of two 24-h dietary recalls during each gestational trimester obtained on non-consecutive days and differentiating weekday v. weekend/holiday. The foods were classified according to the NOVA system into fresh or minimally processed foods and their culinary preparations, processed and UPF and subsequently analysed as a percentage contribution to dietary energy. The outcome was average GWG in the second and in the third trimesters, expressed in g/week.Setting:Botucatu, a medium-sized Brazilian city.Participants:Pregnant women with regular obstetric risk (n 259) undergoing prenatal care in primary healthcare.Results:In a multiple linear regression model, it was found that an increase of 1 percentage point in energy consumption from UPF in the third gestational trimester led to an average increase of 4·17 (95 % CI 0·55; 7·79) g in weekly GWG in this period. There was no association between second-trimester UPF consumption and GWG.Conclusions:Consumption of UPF in the third gestational trimester is positively associated with average weekly GWG in this period.
Keywords: Food processing; Gestational weight gain; Pregnancy; Pregnancy nutrition; Ultra-processed food